1999
DOI: 10.1161/01.hyp.33.6.1379
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Angiogenesis Induced by Human Recombinant Hepatocyte Growth Factor in Rabbit Hind Limb Ischemia Model as Cytokine Supplement Therapy

Abstract: Abstract-Hepatocyte growth factor (HGF) exclusively stimulates the growth of endothelial cells without replication of vascular smooth muscle cells and acts as a survival factor against endothelial cell death. Therefore we hypothesized that a decrease in local vascular HGF might be related to the pathogenesis of peripheral arterial disease. We initially evaluated vascular HGF concentration in the vessels of patients with arteriosclerosis obliterans. Consistent with in vitro findings that hypoxia downregulated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
174
0
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(184 citation statements)
references
References 40 publications
6
174
0
4
Order By: Relevance
“…27 Several recent studies have reported that HGF exhibits angiogenetic actions. Morishita et al 28 reported that treatment with human recombinant HGF improved hindlimb ischemia in rabbits. Human recombinant HGF has been applied in therapeutic angiogenesis, as a cytokine supplement for patients with arteriosclerosis obliterans.…”
Section: Discussionmentioning
confidence: 99%
“…27 Several recent studies have reported that HGF exhibits angiogenetic actions. Morishita et al 28 reported that treatment with human recombinant HGF improved hindlimb ischemia in rabbits. Human recombinant HGF has been applied in therapeutic angiogenesis, as a cytokine supplement for patients with arteriosclerosis obliterans.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous (Paciucci et al, 1998) and our present results showed that production of HGF in pancreatic cancer cell lines is either undetectable or is low and that HGF mediated fibroblast-dependent invasion of pancreatic cancer cells, HGF is likely to be a stromal mediator which affects invasion and probably subsequent metastasis and dissemination of pancreatic cancer cells. Taken together with the notion that HGF is a potent inducer of angiogenesis (Bussolino et al, 1992;Van Belle et al, 1998;Morishita et al, 1999), the abrogation of functional association between HGF and the Met/HGF receptor would be considerable to suppress malignant behaviour of human pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…12,42,43 Briefly, male New Zealand White rabbits (3.5 to 4.0 kg) (Kitayama Rabes, Kyoto, Japan) were used. Four separate injections of 250 g human HGF vector (total 1 mg) locally (intramuscularly into the pretibial muscle of ischemic limb) were performed approximately 2-4 cm below the skin.…”
Section: Rabbit Ischemic Hindlimb Modelmentioning
confidence: 99%
“…12,42,43 Briefly, morphometric analysis of collateral vessel development in the ischemic limb was performed in 4-s angiograms recorded after injection of contrast medium into the internal iliac artery. A grid with 20-mm spaces was placed over the angiogram in the region of the medial thigh.…”
Section: Rabbit Ischemic Hindlimb Modelmentioning
confidence: 99%
See 1 more Smart Citation